Copper–gold sandwich structures on PE and PET and their SERS enhancement effect. Issue 37 (26th April 2017) - Reznickova, Alena; Slepicka, Petr; Nguyenova, Hoang Yen; Kolska, Zdenka; Dendisova, Marcela; Svorcik, Vaclav
Abstract : In this paper we have investigated the SERS effect of gold–copper sandwich structures i.e. the coupling between surface plasmon polaritons supported by the gold grating and localized surface plasmons excited on the grafted copper nanoparticles. Abstract : A Surface Enhanced Raman Spectroscopy (SERS) system with the coupling between surface plasmon polaritons (SPPs) supported by a gold grating and localized surface plasmons (LSPs) excited on grafted copper nanoparticles (CuNPs) was designed and characterized. The excitation of copper nanoparticles–molecules–gold layer sandwich structures was studied under 633 nm wavelength irradiation. Rhodamine 6G (R6G) molecules were added onto SERS substrates and located above and between the CuNPs. Prepared samples were studied by several experimental techniques: goniometry, X-ray photoelectron spectroscopy (XPS), energy dispersive X-ray spectroscopy (EDS), scanning electron microscopy (SEM), atomic force microscopy (AFM) and electrokinetic analysis. Aging of the modified PE and PET was accompanied by an increase in the contact angle, which was due to a reorientation of the molecular polar segments produced during the plasma treatment. XPS and zeta potential measurements indicated that the thiols were chemically bonded to the gold coated polymer surfaces and that the thiols mediate subsequent grafting of Cu nanoparticles. Both XPS and EDS analyses revealed that a higher concentration of grafted copper nanoparticles was achieved on the PET substrate. EDS showed that Cu nanoparticles are homogeneously distributed over the whole polymer surface. The enhancement factor was higher for PE (1.7 × 10 3 ) compared to PET (0.9 × 10 2 ).